Penile Cutaneous Horn Mimicking Carcinoma: A Rare Case - Shah, Amit Kumar; Rai, Ujwal; Jha, Rupesh Kumar; Baskota, Bashu Dev; Vaidya, Monasha; Bhusal, Sagar; Bhagat, Sachin; Adhikari, Bindu (Nepalese Medical Journal, 2022)
Cutaneous horns are cornified hyperkeratotic lesions on the skin, usually present on photo-exposed areas such as the face and scalp. Its presence on the penis is very rare and represents the most unusual site. The role of chronic irritation, phimosis, surgical trauma, and radiotherapy have been implicated in penile horn formation. Penile horns present as elongated, keratinous, white or yellowish projections that range from a few millimeters to centimeters in size arising from the glans penis. Histopathology of the keratotic mass reveals nothing but keratin. One-third of cases of penile horns are associated with underlying malignancies. The standard treatment is electrosurgical excision with the removal of a broad base.